2022
DOI: 10.3389/fphar.2022.995881
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of Parkia biglobosa (Jacq.) R. Br. (Fabaceae) exerts antiepileptogenic, anti-amnesic, and anxiolytic-like effects in mice via mechanisms involving antioxidant and anti-inflammatory pathways

Abstract: Parkia biglobosa (Jacq.) R. Br. (Fabaceae) is a widely distributed tree, used in traditional medicine to treat amebiasis, hookworm infection, ascariasis, asthma, sterility, dental pain, headaches, cardiac disorders, and epilepsy. To date, no study on the effect of an aqueous extract of P. biglobosa on epileptogenesis and associated neuropsychiatric disorders has been undertaken. Therefore, this study aimed to investigate antiepileptogenic-, antiamnesic-, and anxiolytic-like effects of an aqueous extract of P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…In rat brain mitochondrial preparations, it was found to modulate Na + / K + -ATPase activity and improve ROS formation [2]. More recently, an aqueous extract of PB stem bark was found to protect mice from pentylenetetrazole-induced epileptic seizures, amnesia, and anxiety-like behavior while also reducing oxidative stress, inflammation, and degenerated or necrotic neurons in the hippocampus [4]. In vitro, Parkia biglobosa bark extract conferred protection against the cytotoxic, neurotoxic, and hemotoxic effects of venoms from two lethal snakes, Naja nigricollis and Echis ocellatus, and was able to delay mortality from the venoms in mice under in vivo conditions [74].…”
Section: Neuroprotective Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…In rat brain mitochondrial preparations, it was found to modulate Na + / K + -ATPase activity and improve ROS formation [2]. More recently, an aqueous extract of PB stem bark was found to protect mice from pentylenetetrazole-induced epileptic seizures, amnesia, and anxiety-like behavior while also reducing oxidative stress, inflammation, and degenerated or necrotic neurons in the hippocampus [4]. In vitro, Parkia biglobosa bark extract conferred protection against the cytotoxic, neurotoxic, and hemotoxic effects of venoms from two lethal snakes, Naja nigricollis and Echis ocellatus, and was able to delay mortality from the venoms in mice under in vivo conditions [74].…”
Section: Neuroprotective Activitymentioning
confidence: 99%
“…The neuroprotective properties of Parkia biglobosa are thought to be attributed, at least partially, to its GABAergic, antioxidant, and anti-inflammatory signaling mechanisms [4]. Several studies confirmed the antioxidant and anti-inflammatory potentials of the Parkia biglobosa plant in both in vitro and in vivo settings, and some of the therapeutic efficacy of the plant proceeded via these mechanisms [4,75].…”
Section: Mechanisms Of Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For exampel, it has been found to possess analgesic, anti-inflammatory, antimicrobial, antiepileptogenic, anti-amnesic and anxiolytic-like activities. [14][15][16] Additionally, phenolic compounds were found to be the major antimalarial components of P. biglobosa and have shown antimalarial activity against Plasmodium berghei and clinical isolate of Plasmodium falciparum. 17 Furthemore, extracts of fermented seeds of P. biglobosa were reported to exert a hypoglycaemic effect, thus demonstrating an antidiabetic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Along with their renowned status in traditional medicine, their actual pharmacological effects validated by a panoply of studies have also been widely elaborated. For exampel, it has been found to possess analgesic, anti‐inflammatory, antimicrobial, antiepileptogenic, anti‐amnesic and anxiolytic‐like activities 14‐16 . Additionally, phenolic compounds were found to be the major antimalarial components of P. biglobosa and have shown antimalarial activity against Plasmodium berghei and clinical isolate of Plasmodium falciparum 17 .…”
Section: Introductionmentioning
confidence: 99%